Canadian Consensus Guidelines for the Optimal Use of Maraviroc in the Treatment of HIV-Infected Adults. Issue 4 (2010) - Rachlis, Anita; Harris, Marianne; Lalonde, Richard; Shafran, Stephen D; Tremblay, Cécile; Wainberg, Mark A; Walmsley, Sharon
Abstract : BACKGROUND AND OBJECTIVES: A Canadian group, consisting of six physicians and an HIV researcher with significant experience and knowledge in HIV management, reviewed the available data and developed guidelines for Canadian health care providers (who treat HIV infection) on the appropriate use of maraviroc (UK-427, 857) in HIV-infected adults. METHODS: Evidence from the published literature and conference presentations, as well as the expert opinions of the group members were considered and evaluated to develop the recommendations. Feedback on the draft recommendations was obtained from this core group, as well as from four other physicians across Canada with expertise in HIV treatment and experience with the use of maraviroc. The final recommendations represent the core group's consensus agreement once all feedback was considered. RESULTS/CONCLUSIONS: Recommendations were developed to guide physicians and other health care providers in the optimal use of maraviroc. The recommendations were considered in light of the fact that the decision to include maraviroc in an antiretroviral regimen depends not only on issues that concern all antiretroviral agents, such as efficacy, safety, resistance and drug interactions, but also on the issue of viral tropism, which is unique to maraviroc and other CCR5 inhibitors.